Prophylaxis for ophthalmia neonatorum in Brazil: A snapshot using a multi-professional national survey - Miralha, A. L.; Chermont, A. G.; Orlandi, P. P.; Rugolo, L. S. [UNESP]; Sant'Anna, G. (SAGE Publications, 2021)
BACKGROUND: Brazil is a large country with an elevated incidence of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) during pregnancy and variable access to health care. The objective of the study was to identify ophthalmia neonatorum prophylaxis practices in the country. METHODS: A prospective multidisciplinary survey was conducted using a closed social media group. Fifteen questions were developed after literature review. Specific content included categorization of respondents and practices such as type of medication, age at administration, occurrence of clinical and/or chemical conjunctivitis and microbiology identification. Questions were multiple choice, but some allowed written response. RESULTS: A total of 1.015 professionals responded, representing 24 states (92%) and 181 cities; mainly neonatologists (64%) and general pediatricians (21%). 96% of respondents reported performing prophylaxis at their institutions, mostly at birth or <1h of life (99%), and regardless the mode of delivery (73%). Frequently used medications are: 1% silver nitrate (64%), 2.5% povidone iodine (18%) or 10% silver vitelinate (12%), with some regional variations. Occurrence of chemical conjunctivitis was stated by 58% of the respondents and microbiology identification was unusual. CONCLUSIONS: Ophthalmia neonatorum prophylaxis Brazil is almost universal and mainly performed by the use of anti-septic medications, with some regional variability. However, identification and treatment of CT and NG in both parents and newborns is not accomplished.